Antibacterial Activity of Pineapple Peel Eco-enzyme (Ananas comosus L.) on Growth Pseudomonas aeruginosa and Staphylococcus epidermidis - Hendri Hendri; Zulfah Zakiah; Rikhsan Kurniatuhadi (Jurnal Biologi Tropis, 2023)
Eco-enzyme is a fermented product from an organic waste substrate, molasses, and water. Eco-enzyme can be used as antibacterial because it produces organic compounds such as alcohol and acetic acid. Pineapple peel waste (Ananas comosus L.) can be used as an eco-enzyme. This study aimed to test the antibacterial activity of pineapple peel eco enzyme against Pseudomonas aeruginosa and Staphylococcus epidermidis. The study used the method of determining the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MBC) of pineapple peel eco-enzyme with 8 treatment levels namely negative control (aquadest), positive control (ciprofloxacin 5 mg/mL), 3.125%, 6.25 %, 12.5%, 25%, 50%, and 100% eco-enzymes. Based on the research results, it was known that the MIC value of pineapple peel eco-enzyme against P. aeruginosa, and S. epidermidis was 12.5% and 3.125%, respectively. Eco- enzymes from pineapple peel did not show minimum killing concentrations. Eco-enzyme of pineapple peel is only bacteriostatic towards the growth of P. aeruginosa and S. epidermidis bacteria.